A Survey on Immune System in Genetic Engineering and their Applications - Alagirisamy, Mukil (Recent Research Reviews Journal, 2022)
The increasing number of human diseases has become a major global concern. Researchers have found a novel way to defend against some of the deadliest diseases emerging across the globe. Incorporating a genetic modifications in immune cells can result in producing more powerful antibodies. With this technology, researchers have now successfully defended a potentially fatal lung infection. The similar approach might be effective in treating other human diseases. The integration of immune system in genetic engineering is being studied by combining wide range of techniques and organisms from agriculturally relevant plants to other genetic models such as Drosophila to humans. This initiates the research investigations on the rapid advancement of genetic engineering, including advancements in research and education. This study discusses the concept of genetic engineering in the immune system, as well as various types of genetic engineering and their applications. This work discusses about preserving an endangered species while promoting free market environmentalism.